Evolution of Human Immunodeficiency Virus Infection at a Callao Hospital: Evolución de la Infección por Virus de la Inmunodeficiencia Humana en un Hospital del Callao - Cáceda Dávila, Juliocésar (2019)
Objectives: To describe the historical evolution and identify the factors associated with infection by the human immunodeficiency virus in a hospital in the Callao Region. Materials and methods: Analysis of a secondary source. The sample size was census according to the registry of the Program for the Control of Sexually Transmitted Diseases and AIDS (PROCETSS) of the San José Hospital, Callao Region during the period 2004 – 2018. Results: 1944 patients of both sexes participated, with a mean age of 38.99 years (SD = 11.27; Range: 15 to 85). Of the sample, 79% (n = 1536) corresponded to the male sex; 90.4% (n = 1758) were Peruvians and 9.1% (n = 177) Venezuelans. In addition, risk behaviors in adults with 93.0% (n = 1807) and 5.7% (n = 111) men who had sex with men (MSM) have been reported more frequently. The main co-infection with HIV was tuberculosis (TB) with 4.6% (n = 90) and as an opportunistic disease Syphilis with 0.7% (n = 14). Conclusions: The frequency of HIV infection had an increase in the last three years, highlights the presence of foreigners, mainly of Venezuelan nationality. Tuberculosis was the main coinfection and syphilis the most frequent opportunistic disease to HIV infection.  Keywords: HIV; Epidemiology; Transients and Migrants; Peru (Source: MeSH, NLM).